CaractÃ©risation Ã lâ€™aide du SPI de la SÃ©cheresse climatique dans le bassin versant de Ziz (Sud-Est, Maroc) - Mehdaoui, Radouan; Mili, El-Mostafa; Seghir, Aziz (European Scientific Journal, ESJ, 2018)
This paper analyzes the spatial and temporal variability of drought in winter season in an arid geographical gradient located in the eastern edge part of the Moroccan High Atlas especially at the Ziz watershed. Drought period between 1975 and 2013 were analyzed using the Standardized Precipitation Index (SPI) over 12 months for a 38-year scale. The results indicate that the most important drought by intensity and duration occurred during the 1982/84, 1983/84, 2000/01, and 2004/05 periods are generalized on all stations of the basin with a minimum SPI reached -2.77 at the Taous station. The results indicate that drought in winter have been tied to the dominance of dry circulation with the exception of the frequency of thermodynamic and north-eastern disturbances which are considered unstable aerological conditions. Which occur frequently between February and April of each year for the Errachidia station, Hassan Adakhil Dam, Foum Zaabal, Tillicht, M’Zizl, Arfoud and Taouz.